ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN WACANA PADA SISWA KELAS V SD NEGERI SE-GUGUS III KECAMATAN SAIL KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:This research is caused by students less able to read the understanding of the discourse that is less interested students with reading activities, they just read but do not interpret the discourse that is read so they do not understand the content of the discourse, unable to conclude the discourse and determine the main sentence.This makes the student's ability to understand very low reading content. The formulation of this research problem is "How is the ability to read the understanding of discourse on the Grade V Elementary School students as Group III Sail Sub-district Pekanbaru City?" this research is descriptive quantitative research which aims to describe the reading comprehension of discourse in grade V students of SD Negeri as Group III Sail Sub-district Pekanbaru City. The population of this study amounted to 282 students. The sample is taken as much as 50% of the population of 141 students. This research method is descriptive quantitative research. Technique of collecting data by using written test technique using 24 objective objective items that have been validated using anates version V4. The analysis of the research data is done by giving the score on the student answer sheet, calculate the average and present it, recapitulate or create a table that contains the score value, categorize the data, classify, draw conclusions and results obtained reading ability of students understanding. Based on the result of the research, it can be concluded that the reading comprehension of discourse based on the indicator ability to understand the contents of discourse is 79% with good category, and the ability to conclude discourse is 79% with good category, while the ability to determine the main sentence is 69% with enough category. Based on the results of data analysis, the level of reading comprehension ability discourse on the students of grade V SD Negeri as a Class III Sail District Pekanbaru Lesson Year 2016/2017 with a good category with an average percentage of 76%.Keywords: Ability in understanding reading, Discourse